Uji Cemaran Mikroba pada Produk Makanan Ikan - mirza anggriawin; Novriaman Pakpahan (Universitas Teuku Umar, 2022)
Microbes can grow and reproduce in almost a variety of environmental conditions. Food products are one of the environmental conditions suitable for microbial growth. Food products that contain high protein, such as fish food products, can be contaminated by microbes, because they contain nutrients that are suitable for microbial growth and environmental conditions that support growth. Microbial contamination test can be carried out by growing microbes on certain test media such as Mannitol Salt Agar/MSA media which is used to detected Staphylococcus aureus and Eosin Methylene Blue/EMB media to detected bacteria from the coliform group and the presence or absence of Escherichia coli bacteria.